The association between plasma miR-122-5p release pattern at admission and all-cause mortality or shock after out-of-hospital cardiac arrest. (2nd January 2019) - Gilje, Patrik; Frydland, Martin; Bro-Jeppesen, John; Dankiewicz, Josef; Friberg, Hans; Rundgren, Malin; Devaux, Yvan; Stammet, Pascal; Al-Mashat, Mariam; Jögi, Jonas; Kjaergaard, Jesper; Hassager, Christian; et al.
Abstract: Background: Data suggests that the plasma levels of the liver-specific miR-122-5p might both be a marker of cardiogenic shock and a prognostic marker of out-of-hospital cardiac arrest (OHCA). Our aim was to characterize plasma miR-122-5p at admission after OHCA and to assess the association between miR-122-5p and relevant clinical factors such all-cause mortality and shock at admission after OHCA. Methods: In the pilot trial, 10 survivors after OHCA were compared to 10 age- and sex-matched controls. In the main trial, 167 unconscious survivors of OHCA from the Targeted Temperature Management (TTM) trial were included. Results: In the pilot trial, plasma miR-122-5p at admission after OHCA was 400-fold elevated compared to controls. In the main trial, plasma miR-122-5p at admission was independently associated with lactate and bystander cardiopulmonary resuscitation. miR-122-5p at admission was not associated with shock at admission ( p  = 0.14) or all-cause mortality ( p  = 0.35). Target temperature (33 °C vs 36 °C) was not associated with miR-122-5p levels at any time point. Conclusions: After OHCA, miR-122-5p demonstrated a marked acute increase in plasma and was independently associated with lactate and bystander resuscitation. However, miR-122-5p at admission was not associated with all-cause mortality or shock at admission.